Work-Life Stress Management Of Married Women Teachers From Trivandrum District In Kerala - et. al., Aiswarya V Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research study focuses the stress management practices among married women teachers from Government and Self Financing Colleges in Thiruvananthapuram District. The study has conducted, because of need and significance of the situation. Indian constitution is providing equal rights to women and men, besides women have some extra role in their life than a man. Hence their stress level should be significantly different from a man. In this context, the study has conducted a research on family and work related causes which are increasing the stress level, what are the consequences, role and responsibilities of married women teachers, and the solution i.e., factors which are reducing the stress. Descriptive analytical research design was used in the study. Samples were identified through a random selection of government and self financing colleges in Thiruvananthapuram District, Samples were also selected on the basis of simple random sampling method. Data were collected through a structured questionnaire consist of 52 questions under above mentioned research questions. The study will be very helpful to the management and government to make an attention regarding the work life stress among married women teachers and clearly indicating that what the root causes of work life stress.